1359. Human Parainfluenza Epidemiology in Homeless Shelters — King County, Washington. (15th December 2022) - Chow, Eric J; Casto, Amanda M; Roychoudhury, Pavitra; Han, Peter D; Pfau, Brian A; Rogers, Julia H; Cox, Sarah N; Wolf, Caitlin R; Rolfes, Melissa A; Ogokeh, Constance E; Mosites, Emily; Uyeki, Timothy M; et al.
Abstract: Background: Human parainfluenza viruses (HPIV) cause respiratory illness in individuals of all ages. However, HPIV epidemiology data in people experiencing homelessness (PEH) are limited. Methods: We analyzed cross-sectional data from a clinical trial and SARS-CoV-2 surveillance study in 23 homeless shelters in King County, Washington from October 2019-May 2021. Questionnaires and nasal swab specimens were obtained from eligible participants at enrollment. Between October 2019-March 31, 2020, participants included those aged > 3 months with acute respiratory illness. Monthly shelter surveillance was also conducted where participants were recruited regardless of symptoms. With the community spread of SARS-CoV-2, the study design transitioned from a clinical trial to a SARS-CoV-2 surveillance study which expanded enrollment eligibility to include participants with or without symptoms from April 1, 2020, onward. Participants were not followed longitudinally but were permitted to enroll multiple times during the study period. Specimens were tested for HPIV 1-4 and other respiratory viruses using RT-PCR. Results: Among 14, 464 specimens, 32 were HPIV-positive from 29 participants (median age 9 years, range 0.3-64 years; 45% female; 28% Black; 10% with chronic conditions) of which 59% were children. Family shelters had the highest percentage of HPIV infections (Table). HPIV was detected every month before the community spread of SARS-CoV-2. All HPIV-positive samples in May 2021 came from a single family shelter (Figure). Only 67% of HPIV-positive participants had symptoms with runny nose, cough and sore throat the most commonly reported. HPIV co-detection with other respiratory viruses occurred in 19% of HPIV-positive specimens; Rhinovirus co-detection (16%) was the most common. Human Parainfluenza Encounters by Shelter Type Before and After April 1, 2020 Human Parainfluenza Positive Samples by Shelter Type Among Unique Participants Conclusion: HPIV affected PEH of all ages with most cases in shelters with children. Coinciding with community-wide SARS-CoV-2 mitigation efforts, the number of HPIV infections were reduced. However, a cluster of HPIV infections still occurred within one family shelter. Shelter-specific public health measures including non-pharmaceutical interventions used during the COVID-19 pandemic may reduce HPIV infections among residents. Disclosures: Janet A. Englund, MD, AstraZeneca: Advisor/Consultant|AstraZeneca: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Meissa Vaccines: Advisor/Consultant|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant Helen Y. Chu, MD, MPH, Cepheid: Reagents|Ellume: Advisor/Consultant|Gates Ventures: Grant/Research Support|Merck: Advisor/Consultant|Pfizer: Advisor/Consultant.